High stability of a ferredoxin from the hyperthermophilic archaeon A. ambivalens: Involvement of electrostatic interactions and cofactors - Moczygemba, Charmaine (Cold Spring Harbor Laboratory Press, 2001)
The ferredoxin from the thermophilic archaeon Acidianus ambivalens is a small monomeric seven-iron protein with a thermal midpoint (T(m)) of 122°C (pH 7). To gain insight into the basis of its thermostability, we have characterized unfolding reactions induced chemically and thermally at various pHs. Thermal unfolding of this ferredoxin, in the presence of various guanidine hydrochloride (GuHCl) concentrations, yields a linear correlation between unfolding enthalpies (ΔH[T(m)]) and T(m) from which an upper limit for the heat capacity of unfolding (ΔC(P)) was determined to be 3.15 ± 0.1 kJ/(mole • K). Only by the use of the stronger denaturant guanidine thiocyanate (GuSCN) is unfolding of A. ambivalens ferredoxin at pH 7 (20°C) observed ([GuSCN](1/2) = 3.1 M; ΔG(U)[H(2)O] = 79 ± 8 kJ/mole). The protein is, however, less stable at low pH: At pH 2.5, T(m) is 64 ± 1°C, and GuHCl-induced unfolding shows a midpoint at 2.3 M (ΔG(U)[H(2)O] = 20 ± 1 kJ/mole). These results support that electrostatic interactions contribute significantly to the stability. Analysis of the three-dimensional molecular model of the protein shows that there are several possible ion pairs on the surface. In addition, ferredoxin incorporates two iron–sulfur clusters and a zinc ion that all coordinate deprotonated side chains. The zinc remains bound in the unfolded state whereas the iron–sulfur clusters transiently form linear three-iron species (in pH range 2.5 to 10), which are associated with the unfolded polypeptide, before their complete degradation.